Comparing preseason frontal and sagittal plane plyometric programs on vertical jump height in high-school basketball players - King, J. A; Cipriani, D. J. (The Journal of Strength and Conditioning Research, 2010)
The primary purpose of this study was to evaluate whether frontal plane (FP) plyometrics, which are defined as plyometrics dominated with a lateral component, would produce similar increases in vertical jump height (VJH) compared to sagittal plane (SP) Plyometrics. Thirty-two junior varsity and varsity high-school basketball players participated in 6 weeks of plyometric training. Players participated in either FP or SP plyometrics for the entire study. Vertical jump height was measured on 3 occasions: preintervention (baseline), at week 3 of preparatory training, and at week 6 of training. Descriptive statistics were calculated for VJH. A 2-way analysis of variance (ANOVA) with repeated measures was used to test the difference in mean vertical jump scores using FP and SP training modalities. Results showed a significant effect over time for vertical jump (p < 0.001). Moreover, a significant time by protocol interaction was noted (p < 0.032). A 1-way ANOVA demonstrated that only the SP group demonstrated improvements over time, in VJH, p < 0.05. The FP group did not improve statistically. The data from this study suggest that FP plyometric training did not have a significant effect on VJH and significant improvement in VJH was seen in subjects participating in SP plyometrics thus reinforcing the specificity principle of training. However, coaches should implement both types of plyometrics because both training modalities can improve power and quickness among basketball players.